Antioxidant gene-enzyme responses in Medicago truncatula genotypes with different degree of sensitivity to salinity - Fotopoulos, Vasileios; Mhadhbi, Haythem; Mylona, Photini V.; Jebara, Moez; Mohamed, Elarbi Aouani; Polidoros, Alexios N. (My University, 2011)
Antioxidant responses and nodule function of Medicago truncatula genotypes differing in salt tolerance were studied. Salinity effects on nodules were analysed on key nitrogen fixation proteins such as nitrogenase and leghaemoglobin as well as estimating lipid peroxidation levels, and were found more dramatic in the salt-sensitive genotype. Antioxidant enzyme assays for catalase (CAT, EC 1.11.1.6), superoxide dismutase (EC 1.15.1.1), ascorbate peroxidase (EC 1.11.1.11) and guaiacol peroxidase (EC 1.11.1.7) were analysed in nodules, roots and leaves treated with increasing concentrations of NaCl for 24 and 48 h. Symbiosis tolerance level, depending essentially on plant genotype, was closely correlated with differences of enzyme activities, which increased in response to salt stress in nodules (except CAT) and roots, whereas a complex pattern was observed in leaves. Gene expression responses were generally correlated with enzymatic activities in 24-h treated roots in all genotypes. This correlation was lost after 48 h of treatment for the sensitive and the reference genotypes, but it remained positively significant for the tolerant one that manifested a high induction for all tested genes after 48 h of treatment. Indeed, tolerance behaviour could be related to the induction of antioxidant genes in plant roots, leading to more efficient enzyme stimulation and protection. High induction of CAT gene was also distinct in roots of the tolerant genotype and merits further consideration. Thus, part of the salinity tolerance in M. truncatula is related to induction and sustained expression of highly regulated antioxidant mechanisms
Keywords: Water stress; Antioxidants; Glutathione reductase